Preface - Díaz Untoria, José Andrés (Cuban Journal of Agricultural Science, 2016)
The production of scientific knowledge is related to organizations that develop research processes, which are the result of the integration that generates from the needs of society. Along with that, the promotion lies on science spreading and, especially, on facing the pressing problems that demand an effective and accurate response. The work developed at the Instituto de Ciencia Animal (ICA), since its creation, has been based on these considerations. Therefore, this institute is considered as a leader in the development and implementation of impact technologies, with emphasis on nutrition and management of ruminant and non-ruminant animals.